TRADISI TINGKEBAN (SYUKURAN 7 BULANAN) MASYARAKAT JAWA DI DESA SUMBER AGUNG KABUPATEN BANYUASIN (2005-2021) - Fitri Novita Sari; Farida R Wargadalem; Helen Susanti (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
The Tingkeban tradition, or the seven-month thanksgiving celebration, is a local Javanese tradition that is still preserved today, including in Sumber Agung Village, Banyuasin Regency. Sumber Agung Village is a village with a majority Javanese population. This study aims to explain the implementation, symbolic meaning, and cultural values ​​​​of the Tingkeban tradition in the Sumber Agung community. The method used in this study is the historical method with the stages of heuristics, source criticism, interpretation, and historiography. Data collection was carried out through observation and interviews. The results of the study indicate that the Tingkeban tradition is carried out as an expression of gratitude to God Almighty for being given a gift, namely a child, and as a prayer for the safety of the mother and baby. The Tingkeban tradition has several rituals, such as siraman (a bathing ritual), breaking coconuts, making rujak (a fruit salad), brojolan chicken eggs, and so on. This tradition also contains good values ​​​​such as religious and social values, togetherness and mutual cooperation.